A Qualitative Study on Talent Management in Enterprises within the Industry 4.0 Process - Safa Acar; Ahmet SARNIÇ (SEISENSE (PRIVATE) LIMITED, 2024)
Purpose - This study aims to examine the effects of Industry 4.0 on talent management. It is observed that resources are allocated and training programs are organised for the transformation of the workforce in the Industry 4.0 process.Design/Methodology - Qualitative research approach was adopted in the study. Using purposive sampling method, 4 different industrial enterprises were analysed. Data collection process was carried out through face-to-face and online interviews.Findings - Organizations prioritize continuous training and fringe benefits in talent management, while employee involvement in social responsibility projects and teamwork enhances internal communication. In the Industry 4.0 era, maintaining organizational balance and providing diverse opportunities to talented employees are crucial.Practical Implications - The study suggests that implementing 28 different practices such as brand equity, collaboration, work-life balance and career opportunities to retain talent can increase awareness of the impact of Industry 4.0 on HR management. Establishing sector-based standards and models can help researchers in Turkey to implement Industry 4.0 and talent management practices.